How EFL University Students Overcome Anxiety and Build Confidence in Classroom Public Speaking: A Qualitative Study at an Indonesian University - Sheva Syawaludin; Hamzah Puadi Ilyas (Universitas Islam Negeri Palopo, 2026)
Public speaking is widely recognized as one of the most challenging activities for English as a Foreign Language (EFL) learners, particularly in higher education contexts where students are expected to demonstrate both linguistic competence and communication skills. This study investigates how EFL university students overcome anxiety and build confidence when delivering public speaking presentations in classroom settings. The research employed a qualitative descriptive design involving nine students from the English Education Study Program at Universitas Muhammadiyah Prof. DR. HAMKA (UHAMKA), Indonesia, who had completed a Public Speaking course. Data were collected through semi-structured in-depth interviews and analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that students experience various manifestations of Public Speaking Anxiety (PSA), including rapid heartbeat, trembling, overthinking, fear of forgetting content, and concerns about negative evaluation from lecturers and peers. To manage these challenges, students employ several coping strategies such as repeated practice, deep material mastery, preparation of presentation outlines, positive self-talk, deep breathing exercises, strategic pauses, utilization of visual aids, improvisation, code-switching, and seeking social support. Furthermore, positive classroom interactions, particularly supportive peer responses and constructive lecturer feedback, significantly contribute to strengthening students’ confidence and speaking self-efficacy. The study highlights that confidence development is not solely influenced by language proficiency but is also shaped by psychological resilience, preparation strategies, and the learning environment. These findings provide pedagogical implications for creating supportive classroom climates that foster EFL students’ willingness to communicate and public speaking competence.